2014
DOI: 10.1002/2014wr015409
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and diurnal below canopy evaporation in a desert vineyard: Measurements and modeling

Abstract: Evaporation from the soil surface (E) can be a significant source of water loss in arid areas. In sparsely vegetated systems, E is expected to be a function of soil, climate, irrigation regime, precipitation patterns, and plant canopy development and will therefore change dynamically at both daily and seasonal time scales. The objectives of this research were to quantify E in an isolated, drip-irrigated vineyard in an arid environment and to simulate below canopy E using the HYDRUS (2-D/3-D) model. Specific fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 89 publications
(83 reference statements)
4
29
0
Order By: Relevance
“…This model has been previously used to study ET components, for example, for almond (Phogat et al, 2012(Phogat et al, , 2013, maize (Ramos et al, 2012), citrus (Phogat et al, 2014), and other crops (Mei-Xian et al, 2013;González et al, 2015). Recently, Kool et al (2014a) has successfully used this model for the estimation of evaporation losses from a commercial vineyard in combination with short term above canopy measurements of climatic parameters.…”
Section: Introductionmentioning
confidence: 99%
“…This model has been previously used to study ET components, for example, for almond (Phogat et al, 2012(Phogat et al, , 2013, maize (Ramos et al, 2012), citrus (Phogat et al, 2014), and other crops (Mei-Xian et al, 2013;González et al, 2015). Recently, Kool et al (2014a) has successfully used this model for the estimation of evaporation losses from a commercial vineyard in combination with short term above canopy measurements of climatic parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Kool et al . () analysed the variability of E a in a soil vineyard using HYDRUS (2D/3D) (Šimůnek et al ., ). They found that the main sources of E a variability were the soil water content and diurnal patterns which depended strongly on canopy shading.…”
Section: Resultsmentioning
confidence: 94%
“…The rationale for this method was to account for sunlit and shaded soil in the crop interrow, which may comprise substantial positional variation of energy balance terms (e.g., Agam et al, 2012b;Kool et al, 2014b). Because calculation of R N,S includes view factors, it was straightforward to partition the soil surface into its sunlit and shaded components and calculate sunlit and shaded G 0 accordingly.…”
Section: Description Of the Tseb Modelmentioning
confidence: 99%